From diurnal to nocturnal activity: a case study of night-light niche expansion in Agama agama lizards. Issue 5 (3rd September 2021) - Amadi, Nioking; Luiselli, Luca; Belema, Robert; Awala Nyiwale, Grace; Wala, Chimela; Urubia, Nwaiwu; Meek, Roger
Abstract : Most species of lizard are either diurnal or nocturnal, and it is extremely rare to find species that operate both diurnally and nocturnally, or that may shift from diurnality to partial nocturnality when conditions allow. However, niche expansion from diurnal to nocturnal habits (often referred to as the night-light niche) has rarely been reported in lizards (mainly in Anoles), and mostly through anecdotal reports. In West Africa, the rainbow lizard Agama agama is a conspicuous species across the region but also lives in suburban areas of towns and villages. It is a diurnal sun-basker operating at relatively high body temperatures of 36 °C and higher. In this paper, we describe a night-light niche expansion, i.e. nocturnal foraging and thermoregulation, in a small number of A. agama populations living in suburban areas. These lizards utilised radiant heat from incandescent light bulbs situated on the walls of buildings to mostly achieve target body temperatures and forage for and fed on five different groups of invertebrates. Foraging lizards had significantly higher body temperatures than inactive lizards. However, variance in body temperature was significantly greater in foraging lizards than in inactive lizards probably due to the necessity to shuttle between the incandescent night lights and cooler foraging areas during activity, a known cost of thermoregulation. Regression analysis of body temperatures against time of night in foraging lizards supported the notion that the lizards were maintaining body temperatures by actively thermoregulating whilst in inactive non-basking resting lizards during the same time period body temperatures declined. Although our results indicate a potential thermoregulatory benefit from using the night-light shift, we cannot be certain that this benefit is the direct cause of the shift, rather than an additional advantage when foraging.